Nogais of the Azov region as an example of the imperial policy on the sedenterization of nomadic societies at the end of the 18th – 60s of the 19th century - Aigul, Dzhumagulova (Kavkazologiya, 2022)
The article researches the transition of Nogai nomadic societies, transferred by the supreme cen-tral authorities of the Russian Empire at the end of the XVIII century from the Pre-Caucasian and Pre-Kuban prairies to the Melitopol district of the Taurida region to a settled state. This article reveals the climatic, socio-economic and political factors influencing the successful process of transition of nomadic societies into a settled state at the beginning of the XIX century. Particular attention is paid to the role of the central and regional apparatus of state authorities on the trans-formation of traditional forms of life, everyday life and economic sectors of the Nogais and the period of their adaptation to the general imperial realities. The author draws attention to the suc-cessful results of the sedentarization of nomadic Nogais implemented by the Russian administra-tion in the first quarter of the XIX century cannot be assessed unambiguously, because of the mass exodus of Nogais living in the Tauride province to the Ottoman Empire in the 60s of the XIX cen-tury.